Molecular Detection of Insecticide Resistance Mutations in Anopheles gambiae from Sierra Leone Using Multiplex SNaPshot and Sequencing - Yin, Jianhai; Yamba, Frederick; Zheng, Canjun; Zhou, Shuisen; Smith, Samuel Juana; Wang, Lili; Li, Hongmei; Xia, Zhigui; Xiao, Ning (Frontiers in Cellular and Infection Microbiology, 2021)
Vector control interventions including long-lasting insecticidal nets and indoor residual spraying are important for malaria control and elimination. And effectiveness of these interventions depends entirely on the high level of susceptibility of malaria vectors to insecticides. However, the insecticide resistance in majority of mosquito vector species across African countries is a serious threat to the success of vector control efforts with the extensive use of insecticides, while no data on insecticide resistance was reported from Sierra Leone in the past decade. In the present study, the polymerase chain reaction was applied for the identification of species of 757 dry adult female Anopheles gambiae mosquitoes reared from larvae collected from four districts in Sierra Leone during May and June 2018. And the mutations of kdr, rdl, ace-1 genes in An. gambiae were detected using SNaPshot and sequencing. As a result, one sample from Western Area Rural district belonged to Anopheles melas, and 748 An. gambiae were identified. Furthermore, the rdl mutations, kdr west mutations and ace-1 mutation were found. The overall frequency was 35.7%, 0.3%, 97.6% and 4.5% in A296G rdl, A296S rdl, kdrW and ace-1, respectively. The frequencies of A296G rdl mutation (P < 0.001), kdrW mutation (P = 0.001) and ace-1 mutation (P < 0.001) were unevenly distributed in four districts, respectively, while no statistical significance was found in A296S rdl mutation (P = 0.868). In addition, multiple resistance patterns were also found. In conclusion, multiple mutations involved in insecticide resistance in An. gambiae populations in Sierra Leone were detected in the kdrW, A296G rdl and ace-1 alleles in the present study. It is necessary to monitor vector susceptibility levels to insecticides used in this country, and update the insecticide resistance monitoring and management strategy.